PENINGKATAN KREATIVITAS PESERTA DIDIK MELALUI MEDIA TALI PADA KEGIATAN EKSTRA KURIKULER PRAMUKA DI MI AL-IKHLASH SURABAYA: PENINGKATAN KREATIVITAS PESERTA DIDIK MELALUI MEDIA TALI PADA KEGIATAN EKSTRA KURIKULER PRAMUKA DI MI AL-IKHLASH SURABAYA - Taseman, Taseman; Ali Doflir, Muhammad; Rua Indah, Novia Ayu (Al Tadib : Jurnal Ilmu Pendidikan, 2021)
Each student's creativity needs to be developed and sharpened so that they are increasingly trained. A lot of creativity can be created from the objects around us, examples of the development of creativity are scouting exercises, in our scouts we are also taught how to use items that are not used. And these goods have a sale value. Like a rope, the material in scouting is called rigging, and in teaching scouting there are many obstacles that must be overcome professionally. Like the coach who suddenly had an activity so he could not fill the material on that day. We as coaches must be agile in dealing with such problems. Moreover, during the rainy season and anti-body students are low. Then it can trigger a decline in health. Scouts also don't always teach the material, in scouts we are also taught to be students of good character, and to be students who are based on the Dasa Dharma. Creativity and noble character is one of the goals of scout education at MI Al-Ihklash Surabaya